First-in-human, open-label dose-escalation and dose-expansion study of the safety, pharmacokinetics, and antitumor effects of an oral ALK inhibitor ASP3026 in patients with advanced solid tumors. Issue 1 (December 2016) - Li, Tianhong; LoRusso, Patricia; Maitland, Michael; Ou, Sai-Hong; Bahceci, Erkut; Ball, Howard; Park, Jung; Yuen, Geoffrey; Tolcher, Anthony
Abstract Background ASP3026 is a second-generation anaplastic lymphoma kinase (ALK) inhibitor that has potent in vitro activity against crizotinib-resistantALK -positive tumors. This open-label, multicenter, first-in-human phase I study (NCT01284192 ) assessed the safety, pharmacokinetic profile, and antitumor activity of ASP3026. Methods Advanced solid tumor patients received oral ASP3026 in 3 + 3 dose-escalation cohorts at doses of 25–800 mg once daily in 28-day cycles. The endpoints were to identify the maximum tolerated dose (MTD), the recommended phase II dose (RP2D), and the pharmacokinetic profile of ASP3026. A phase Ib expansion cohort enrolled patients with metastatic, crizotinib-resistantALK -positive solid tumors at the RP2D, and response was evaluated by RECIST 1.1. Results The dose-escalation cohort enrolled 33 patients, including three crizotinib-resistant, ALK -positive patients, and the dose-expansion cohort enrolled another 13 crizotinib-resistant, ALK -positive non-small cell lung cancer (NSCLC) patients. ASP3026 demonstrated both linear pharmacokinetics and dose-proportional exposure for area under the plasma concentration–time curve and maximum concentration observed with a median terminal half-life of 35 h, supporting the daily dosing. Grade 3 rash and elevated transaminase concentrations were dose-limiting toxicities observed at 800 mg; hence, 525 mg daily was the MTD and RP2D. The most common treatment-related adverse events were nausea (38 %), fatigue (35 %), and vomiting (35 %). Among the 16 patients with crizotinib-resistantALK -positive tumors (15 NSCLC, 1 neuroblastoma), eight patients achieved partial response (overall response rate 50 %; 95 % confidence interval 25–75 %) and seven patients (44 %) achieved stable disease. Conclusions ASP3026 was well tolerated and had therapeutic activity in patients with crizotinib-resistantALK -positive advanced tumors. Trial registration ClinTrials.gov:NCT01284192